Heterotrophic nitrogen removal by a newly-isolated alkalitolerant microorganism, Serratia marcescens W5. (July 2016) - Wang, Teng; Dang, Qifeng; Liu, Chengsheng; Yan, Jingquan; Fan, Bing; Cha, Dongsu; Yin, Yanyan; Zhang, Yubei
Highlights: A new microbe, Serratia marcescens W5 was successfully isolated & further studied. Serratia marcescens W5 had a maximum ammonium removal rate of 514.13 mg L −1 d −1 . W5 showed great ammonium removal abilities in a wide range of pH, Temp. & salinity. Nitrite & nitrate were efficiently utilized by W5 only in the presence of ammonium. Abstract: A new microbe, Serratia marcescens W5 was successfully isolated. Its feasibility in purification of excessively nitrogen-containing wastewater was evaluated using inorganic nitrogen media. Single factor tests showed that W5 exhibited high ammonium removal rates (above 80%) under different culture conditions (pH 7–10, C/N ratios of 6–20, 15–35 °C, 0–2.5% of salinity, respectively). Besides various organic carbon sources, W5 was able to utilize calcium carbonate with 28.05% of ammonium removed. Further experiments indicated that W5 was capable of resisting high-strength ammonium (1200 mg/L) with the maximum removal rate of 514.13 mg L −1 d −1 . The nitrogen removal pathway of W5 was also tested, showing that both nitrite and nitrate were efficiently removed only in the presence of ammonium, with hydroxylamine as intermediate, which was different from the conventional nitrogen removal pathway. All the results verified that W5 was a good candidate for the purification of excessively nitrogenous wastewater.